The minimal domain of adipose triglyceride lipase (ATGL) ranges until leucine 254 and can be activated and inhibited by CGI-58 and G0S2, respectively. - Irina Cornaciu; Andras Boeszoermenyi; Hanna Lindermuth; Harald M Nagy; Ines K Cerk; Catharina Ebner; Barbara Salzburger; Astrid Gruber; Martina Schweiger; Rudolf Zechner; Achim Lass; Robert Zimmermann; et al. (PLoS ONE)
Adipose triglyceride lipase (ATGL) is the rate-limiting enzyme of lipolysis. ATGL specifically hydrolyzes triacylglycerols (TGs), thereby generating diacylglycerols and free fatty acids. ATGL's enzymatic activity is co-activated by the protein comparative gene identification-58 (CGI-58) and inhibited by the protein G0/G1 switch gene 2 (G0S2). The enzyme is predicted to act through a catalytic dyad (Ser47, Asp166) located within the conserved patatin domain (Ile10-Leu178). Yet, neither an experimentally determined 3D structure nor a model of ATGL is currently available, which would help to understand how CGI-58 and G0S2 modulate ATGL's activity. In this study we determined the minimal active domain of ATGL. This minimal fragment of ATGL could still be activated and inhibited by CGI-58 and G0S2, respectively. Furthermore, we show that this minimal domain is sufficient for protein-protein interaction of ATGL with its regulatory proteins. Based on these data, we generated a 3D homology model for the minimal domain. It strengthens our experimental finding that amino acids between Leu178 and Leu254 are essential for the formation of a stable protein domain related to the patatin fold. Our data provide insights into the structure-function relationship of ATGL and indicate higher structural similarities in the N-terminal halves of mammalian patatin-like phospholipase domain containing proteins, (PNPLA1, -2,- 3 and -5) than originally anticipated.